Implementation of Academic Supervision of Madrasah Supervisors in Improving the Quality of Islamic Education Learning in Gowa Regency - Azis Masang; Rusli Malli; Amirah Mawardi (Pelopor Publikasi Akademika, 2024)
This study aims to explore the implementation of Academic Supervision by Madrasah Supervisors in Gowa Regency in improving the quality of Islamic Religious Education (PAI) learning. Academic supervision is considered a solution to improve teacher competence, but its implementation is still considered low. This research method is field research involving interviews, observation, and documentation studies. The results showed that academic supervision planning is the primary responsibility of madrasah supervisors, with the Academic Supervision Plan (RPA) as a critical instrument. Despite facing limitations such as busyness, supervisors try to be efficient by using the Bimlat. The active participation of PAI teachers in supervision planning is recognized as a crucial factor in improving the quality of PAI learning. The initial year meeting involved PAI teachers in preparing an academic supervision work plan, creating a collaborative spirit. Evaluation and analysis of supervision results and follow-up are still a challenge. Time constraints are a bottleneck, and immediate feedback is given after supervision, but comprehensive follow-up has not yet been fully implemented. This research implies that academic supervision needs to be carried out through planned, systematic, and local culture-based stages,